AlGaN/GaN metal–insulator–semiconductor high-electron mobility transistors with high on/off current ratio of over 5 × 1010 achieved by ozone pretreatment and using ozone oxidant for Al2O3 gate insulator. (11th November 2016) - Tokuda, Hirokuni; Asubar, Joel T.; Kuzuhara, Masaaki
Abstract: This letter describes DC characteristics of AlGaN/GaN metal–insulator–semiconductor high-electron-mobility transistors (MIS-HEMTs) with Al2 O3 deposited by atomic layer deposition (ALD) as gate dielectric. Comparison was made for the samples deposited using ozone (O3 ) or water as oxidant. The effect of pretreatment, where O3 was solely supplied prior to depositing Al2 O3, was also investigated. The MIS-HEMT with O3 pretreatment and Al2 O3 gate dielectric deposited using O3 as the oxidant exhibited the most desirable characteristics with an excellent high on/off current ratio of 7.1 × 10 10, and a low sub-threshold swing (SS) of 73 mV/dec.